Implementasi Kurikulum Satuan Pendidikan Kerjasama dalam Pelaksanaan Pembelajaran Global Perspective (Studi kasus SMA Nation Star Academy Surabaya) - Budiono, Catur Ambyah; W, Warsono; Jacky, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted in Nation Star Academy Senior Secondary School or High School, Surabaya City, West Beautiful Dharmahusada Road VI No. 1 Mojo Gubeng District. Based on the type of data that has been researched, this study uses a qualitative approach with reference to previous studies. Data collection employed the methods of interviews, observation, literature study, as well as documentation. The study was analyzed qualitatively. Qualitative data analysis, which is inductive in nature, is an analysis based on the data or information obtained. Analysis consists of three simultaneously occurring activity streams namely: data reduction, data presentation, as well as conclusion drawing or commonly referred to as verification. The results of the study showed that, the implementation of curriculum policies in Nation Star Academy High School Surabaya can be analyzed through the three aspects of responsiveness put forward by Bloom: verbal, motor, and cognitive. Overall, despite encountering challenges in implementation, the curriculum policy has great potential to improve the quality of education at Nation Star Academy High School Surabaya. To support its success, improved coordination among teachers, ongoing training, periodic evaluation, as well as the development of educational resources that further support this policy-based learning process are needed.